Analysis of the status of creative tourism components in the metropolises of Tabriz as the capital of tourism in Islamic countries - Masoud Safair Pour; Yahia Jafari (تحقیقات کاربردی علوم جغرافیایی)
Creating a creative city and creative tourism are considered as one of the most successful urban management practices to attract material and immaterial capital. In pursuit of this goal, Miran-e-Shahriy has been developing a creative tourism infrastructure. The metropolis of Tabriz has also been selected as the capital of the Islamic countries for tourism in 2018, with its huge potential. The purpose of this study is to investigate the role of effective factors on the realization of creative tourism and the infrastructure of this city in the pursuit of this goal. The type of research, applied and its descriptive-analytical method is correlation. Data analysis was done by statistical tests. Prioritization of the elements of the creative city and urban areas is in line with the development of creative tourism, using network analysis and topsis models. The statistical population of the study is 758421 people living in Tabriz's 10th district. Of these, 384 people have been selected using Cochran's formula and simple random sampling.The variable of this research is 10 criteria with 16 sub-criteria. The results of statistical tests showed that all components of the creative city have a significant correlation with the level of creativity of urban areas of Tabriz. In this regard, the two variables of creativity and creative class infrastructure were the most correlated with 0.583 and 0.557. The results of the ANP model showed that the criteria for creativity and creative class infrastructure with the score of 0.389 and 0.269 have the most importance in the formation of the creative city. The study of the status of different regions of the city according to the indicators of the creative city showed that eight of them are more suitable due to the concentration of historical works, shopping centers and recreation centers. As a result, practical solutions have been developed for using urban infrastructure to form a creative city and identify Tabriz to Islamic countries.